Praktik Sanda sebagai Akad Gadai dan Tinjauannya dalam Hukum Islam - Mega Dini; Hendra Karunia Agustine; Eka (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2026)
Sanda is a form of pawn transaction practiced by the community of Cinangka Village, Serang Regency, Banten Province. In this practice, the lender obtains benefits from the collateral pledged by the borrower while the debt remains unpaid. Furthermore, if the borrower fails to redeem the debt, the collateral in the form of agricultural land is transferred to the lender as debt settlement, resulting in a transfer of ownership. This study aims to analyze the mechanism of sanda as a pawn contract and examine its conformity with the principles of Islamic law. The research employs a qualitative method combining field research and library research. Data were collected through interviews, documentation, and literature studies from relevant books and scholarly articles. The findings reveal three main issues in the implementation of sanda. First, the absence of a clearly determined repayment period at the time of the contract. Second, the utilization of the pledged property by the lender without proportional compensation. Third, the provision that the collateral may be used as debt repayment if the borrower fails to settle the debt, even when the value of the collateral exceeds the amount owed. From the perspective of Islamic law, the practice of sanda is not fully consistent with the principles of rahn (Islamic pawn). The ambiguity regarding the repayment period contains elements of gharar (uncertainty), the utilization of collateral by the pledgee is impermissible when the benefits received are disproportionate to the costs incurred, and the transfer of ownership of the collateral as debt settlement contradicts the principle of justice because collateral serves merely as security for debt rather than as a means of repayment. Therefore, the practice of sanda in Cinangka Village requires adjustment to align with the principles of Islamic law.